A review on high-performance SiCf/SiC composites prepared by PIP process - Jingyao Hu; Chidong Liu; Fang Ye; Laifei Cheng; Yucong Wei (Journal of Materials Research and Technology)
Silicon carbide fiber-reinforced silicon carbide ceramic matrix composites (SiCf/SiC) are considered as a promising material for aero-engine hot-end structural components. The polymer infiltration and pyrolysis (PIP) process offers the benefits of high cost-effectiveness, adjustable preparation temperatures, and the ability to fabricate components with complex shapes. The manufacture of high-performance SiCf/SiC composites using the PIP process has become a research focus. This review briefly generalizes the synthesis methods of polycarbosilane and the specific process of polycarbosilane converting into SiC ceramics during pyrolysis. In addition, the physical and mechanical properties of SiCf/SiC composites prepared by the PIP process in recent years are discussed. Furthermore, this review summarizes some improvements to address the shortcomings of the PIP process, including adding fillers and combining other processes to assist the PIP process. At last, the future development trend of high-performance SiCf/SiC composites prepared by the PIP process is prospected.